A widespread sequence-specific mRNA decay pathway mediated by hnRNPs A1 and A2/B1 - Geissler, Rene (Genes Dev, 2016)
3′-untranslated regions (UTRs) specify post-transcriptional fates of mammalian messenger RNAs (mRNAs), yet knowledge of the underlying sequences and mechanisms is largely incomplete. Here, we identify two related novel 3′ UTR motifs in mammals that specify transcript degradation. These motifs are interchangeable and active only within 3′ UTRs, where they are often preferentially conserved; furthermore, they are found in hundreds of transcripts, many encoding regulatory proteins. We found that degradation occurs via mRNA deadenylation, mediated by the CCR4–NOT complex. We purified trans factors that recognize the motifs and identified heterogeneous nuclear ribonucleoproteins (hnRNPs) A1 and A2/B1, which are required for transcript degradation, acting in a previously unknown manner. We used RNA sequencing (RNA-seq) to confirm hnRNP A1 and A2/B1 motif-dependent roles genome-wide, profiling cells depleted of these factors singly and in combination. Interestingly, the motifs are most active within the distal portion of 3′ UTRs, suggesting that their role in gene regulation can be modulated by alternative processing, resulting in shorter 3′ UTRs.